The effect of mud-bath therapy on bone status in rats during adjuvant subchronic arthritis - Živná, Helena; Maric, Ljiljana; Gradošová, Iveta; Švejkovská, Klára; Hubená, Soňa; Živný, Pavel (Acta Medica, 2012)
Introduction: We studied influence of mud-bath on bone status in male Wistar rats with subchronic arthritis. Methods: Arthritis was induced by 2 subplantar injections of Freund's adjuvans with heat-killed Streptoccocus pyogenes into paw. Groups: intact (int) on chippings; (con) arthritis on chippings; (san38) arthritis on hot sand; (mu38) arthritis on hot mud; (mu21) arthritis on mild mud. Bone mineral density (BMD, g/cm2) was measured by dual energy X-ray absorptiometry and femurs were tested biomechanically. Bone markers osteocalcin (OC), PINP and CTX were analysed in bone. Results: BMD of right femur decreased vs. left in san38 (p = 0.030) and mu38 (p = 0.047). Fracture load of right/left femur (N) decreased in experimental groups, significantly in san38 (p = 0.05). Fracture threshold of neck decreased in right vs. left in experimental groups, but significantly in san38 (p = 0.05). OC decreased in mu38 vs. con (1.84 ± 0.14/2.62 ± 0.23). PINP decreased in int vs. san38 (p = 0.005) and mu21 (p < 0.001). CTX decreased in int vs. mu38 (p = 0.006) and mu21 (p = 0.005). Conclusion: The hot bath appears indifferent in relation to osteoporosis, while cold mud-bath shows good effect on bone metabolism. The cold mud-baths help to reduce arthritic inflammation and pain and thereby lead to higher mobility with positive consequence on bone.
Keywords: potkani Wistar; fraktury femuru; kosti a kostní tkáň; Biomechanical Phenomena; statistika jako téma; Disease Models, Animal; modely nemocí na zvířatech; Bone Density; artritida experimentální; osteokalcin; Animal Experimentation; biomechanika; Rats, Wistar; Bone and Bones; Statistics as Topic; terapie bahnem; Mud Therapy; Femoral Fractures; Osteoporosis; Animals; zvířata; osteoporóza; Osteocalcin; kostní denzita; experimenty na zvířatech; Arthritis, Experimental